PROFIL STRATEGI BELAJAR SRL KOMPONEN KOGNITIF DALAM MEMPERSIAPKAN UJIAN SOCA SELAMA MASA PEMBELAJARAN TATAP MUKA TERBATAS - Widiartini, Catharina; Hidayah, Arfi Nurul; Ardansyah, Marsya Bunga Dis (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
Background: SOCA is an assessment method which tests students' critical thinking, clinical reasoning, and communication skills. SRL (self-regulated learning) cognitive component is a crucial learning-strategies which is useful in processing and storing information on preparing SOCA. SRL determines presage factors in learning environment change. The learning process has changed since the COVID-19 pandemic, which was originally fully online to PTMT. These environmental changes regulate an important role in the SOCA preparation process; thus, this profile of the learning process is not only prominent for monitoring and evaluating in policy making by institution, but also for self-evaluating by respondents. Objective: To find profile of SRL learning strategies for cognitive components in preparing SOCA from FK Unsoed students’ during limited face-to-face learning method in 2021/2022. Methods: This quantitative-observational-descriptive study uses primary data from a questionnaire